Advancements in fungal and fungi-like diversity with a new species and updated records - Chen, Yanpeng; Liao, Yuechi; Shami, Ashwag; Alharbi, Nada K.; Liu, Jian-Kui; Maharachchikumbura, Sajeewa S. N. (Phytotaxa, 2025)
Sichuan Province is a biodiversity hotspot known for its rich flora and fauna; however, it has received limited attention regarding fungal diversity. Recent studies have reported numerous novel fungal species from this region, underscoring its untapped potential. The present study contributes to a long-term investigation of fungi and fungi-like organisms in Sichuan Province. We identified two filamentous fungal taxa, Neomyrmecridium sichuanense sp. nov. and Trimmatostroma salicis, through multilocus phylogenetic analyses and morphological diagnosis. Additionally, Paradiacheopsis longipes, a fungi-like organism, was identified based solely on morphological data. N. sichuanense was determined as a new species, differentiated from phylogenetically closely related species by its 91% ITS sequence identity and smaller conidia. Additionally, T. salicis was reported from China for the first time, while P. longipes was updated with a detailed description and illustration. These discoveries enhance our comprehension of the diversity of fungi and fungi-like organisms in Sichuan, underscoring the significance of ongoing exploration and documentation within this relatively unexamined region.